Analisis Strategi Integrated Marketing Communication dalam Penerimaan Peserta Didik Baru di Lembaga Pendidikan - Kuswantoro Kuswantoro (Institut Agama Islam Negeri Purwokerto, 2016)
AbstractEducational institutions in general public schools rarely use marketingstrategies in getting new students. This is due to one of them because thepublic school when the acceptance of new learners have been flooded withnew prospective students, but different things happen in the average ofprivate schools. The purpose of this paper is to examine how IntegratedMarketing Communication (IMC) which consists of advertising, salespromotion, public relations & publicity and direct marketing, of NewStudent Admissions (PPDB) in private schools, especially the newlyestablished private schools. Due to the reality in society many publicperceptions that private schools are less interested in society because theythink that private schools do not have good quality compared to stateschools. For that it needs new breakthroughs to increase the number of newlearners in accordance with the target expected by the educational institutionis through Integrated Marketing Communication (IMC).AbstrakLembaga pendidikan secara umum terutama di sekolah-sekolah negeri jarangsekali menggunakan strategi marketing dalam mendapatkan siswa-siswibaru.Ini disebabkan salah satunya karena sekolah negeri ketika penerimaanpeserta didik baru sudah kebanjiran calon siswa baru, tetapi hal berbedaterjadi di rata-rata sekolah swasta.Tujuan penulisan ini adalah mengkajibagaimana Integrated Marketing Communication (IMC) yang terdiri dariadvertising, sales promotion, public relation & publicity serta directmarketing, terhadap Penerimaan Peserta Didik Baru (PPDB) di sekolahsekolahswasta terutama sekolah swasta yang baru berdiri.Karena realita yangterjadi di masyarakat banyak persepsi-persepsi masyarakat bahwa sekolahsekolahswasta kurang di minati oleh masyarakat karena menganggap bahwa sekolah-sekolah swasta tidak memiliki kualitas yang bagus di bandingkansekolah-sekolah negeri.Untuk itu perlu adanya terobosan-terobosan baruguna meningkatkan jumlah peserta didik baru sesuai dengan target yangdiharapkan oleh lembaga pendidikan tersebut yaitu melalui IntegratedMarketing Communication (IMC).